The Second-Year Students’ Writing Ability in Recount Text: The Use of Small Group Activities - Nur Faizah Akidah; Nurul Fachrunnisa (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2022)
This research aims to determine whether or not the use of small group activities enhances the second-year students’ writing ability of SMP Negeri 21 Makassar in writing recount text in terms of its ideas, organization, style, and convention. The research used the pre- experimental approach, using one group pre-test and post-test design. The variables of the study are independent and dependent. The Independent variable is the use of small group activities, while the dependent variable is enhancing students’ ability to write recount text. The research population was consisted of students of SMP NEGERI 21 Makassar, which consists of nine classes. The research applied a cluster random sampling technique, and the sample consisted of 36 students. The study's findings revealed that the writing ability of the second-year students of SMP Negeri 21 Makassar is improved by using small group activities as a technique in teaching English. Based on the components of the recount scoring rubric, the highest student improvement was ideas. It was demonstrated that the mean score of the students’ post-test (64.86) was higher than the mean score of the pre-test (40.72). The t-test result (14.170) was more than the t-table result (2.042). It implies a substantial improvement in the student’s writing ability before and after employing small group activities in writing recount text for the second-year students of SMPN 21 Makassar.